2000
DOI: 10.1038/sj.cgt.7700144
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of breast carcinoma tumor growth and lung colonization by overexpression of the soluble urokinase-type plasminogen activator receptor (CD87)

Abstract: The serine protease urokinase-type plasminogen activator, uPA, when bound to its specific receptor, uPAR (CD87), plays a significant role in tumor cell invasion and metastasis. In breast cancer, enhanced uPA antigen in the primary tumor is correlated with poor prognosis of the patient. In an in vivo nude mouse model, we tested tumor growth and metastasis of human breast carcinoma cells that had been transfected with an expression plasmid encoding a soluble form of uPAR (suPAR). We explored, whether suPAR/uPA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 20 publications
2
35
1
Order By: Relevance
“…Lung is a major site for metastatic spread of cancer cells during breast cancer progression [28,29]. In order to explore the impact of uPAR-del4/5 overexpression in vivo, we intravenously injected mice with MDA-MB-231-vector, -uPAR-WT, or -uPAR-del4/5 cells and analyzed incidence, number, and size of nodules of experimental lung metastases.…”
Section: In Vivo Phenotype Of Upar-del4/5 Overexpressing Breast Cancementioning
confidence: 99%
“…Lung is a major site for metastatic spread of cancer cells during breast cancer progression [28,29]. In order to explore the impact of uPAR-del4/5 overexpression in vivo, we intravenously injected mice with MDA-MB-231-vector, -uPAR-WT, or -uPAR-del4/5 cells and analyzed incidence, number, and size of nodules of experimental lung metastases.…”
Section: In Vivo Phenotype Of Upar-del4/5 Overexpressing Breast Cancementioning
confidence: 99%
“…For example, Marimastat can cause severe joint pain, which has to be minimized by reducing the dose, but at the expense of e cacy (Steward and Thomas, 2000). Secondly, MMPI, like TIMP, can also function in favor of tumor growth by up-regulation of angiogenic factors (Kruger et al, 2001) or by inhibiting the angiostatin or endostatinconverting MMPs (Patterson and Sang, 1997;Pozzi et al, 2000) and therefore playing a positive role in angiogenesis. In consistence with this scenario, an induction of liver metastasis was reported on intraperitoneally growing esophagus and ovarial carcinoma, intravenously inoculated T-cell lymphoma cells, and human breast carcinoma, when the mice were treated daily with Batimastat (Kruger et al, 2001).…”
Section: Protumormentioning
confidence: 99%
“…In this context, it has been reported that patients with small cell lung cancer receiving the MMP inhibitor Tanomastat (BAY12-9566) did worse than controls (Bayer, Corp., 1999), and treatment with the gelatinase inhibitor Prinomastat in patients with non small cell lung cancer did not lead to any bene®cial e ect as compared to the placebo group (Agouron, 2000). Finally, in vivo treatment with Batimastat resulted in increased liver metastases of breast carcinoma and T-cell lymphoma in nude or syngeneic mice (Kruger et al, 2001).…”
Section: Introductionmentioning
confidence: 97%